The Role Of Syllogistic Argument In Legal Reasoning - Barrios Jansen Ferreira, Francisco José (2016)
It is a trend in legal theory, and particularly in the Brazilian legal and academic literature, the positioning that deductive reasoning, in the form of syllogism, was overcome by the adoption of legal principles in the decision, becoming now an obsolete method. However, this analysis does not provide an adequate description of the legal practice. This paper intends to demonstrate the central and contemporary role of syllogism in legal argument as an important tool to justify a court decision.